Basic hands-on introduction to holography for ophthalmology and optometry undergraduate students - Costa, Manuel F. M. (2020)
The three-dimensional visualization of objects and structures is very important in a number of situations also because that is how we normally see. Holography is a well-established way of creating 3D images of real objects. The technical and scientific developments over last decades in this field turn holography, either analogue and digital, a very powerful tool in many different applications including in medicine. Important advances were made also in domains involving eyesight and the eye like optometry, ophthalmology and ophthalmic optics.